2021
DOI: 10.1001/jamanetworkopen.2021.19141
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated With State-Specific Medicaid Expansion and Receipt of Autologous Breast Reconstruction Among Patients Undergoing Mastectomy

Abstract: Key Points Question What is the association between the Patient Protection and Affordable Care Act’s state-specific Medicaid expansion and the use of autologous breast reconstruction? Findings In this national cross-sectional study of 45 850 patients who underwent mastectomy and 9215 patients who received autologous breast reconstruction, although the proportion of patients undergoing autologous breast reconstruction increased from 18.1% to 23.0% over the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Although previous studies have identified geographic practice variability in breast reconstruction in relation to plastic surgeon density and insurance coverage, 16 , 17 our study is one of the first to investigate guideline awareness on a regional level. Awareness of autologous breast reconstruction guidelines was regionally variable, with respondents from the Mountain West, Northeast, and Southwest regions reporting higher relative rates than their geographic counterparts.…”
Section: Discussionmentioning
confidence: 95%
“…Although previous studies have identified geographic practice variability in breast reconstruction in relation to plastic surgeon density and insurance coverage, 16 , 17 our study is one of the first to investigate guideline awareness on a regional level. Awareness of autologous breast reconstruction guidelines was regionally variable, with respondents from the Mountain West, Northeast, and Southwest regions reporting higher relative rates than their geographic counterparts.…”
Section: Discussionmentioning
confidence: 95%
“…This study has limitations. Our findings are dependent on the accuracy of the data coded in the database; however, HCUP is one of the largest longitudinal hospital databases in the United States and is commonly used in the surgical literature to study health care outcomes . Additionally, the implicit bias data used in this study do not provide any information on potential confounding variables, ie, education, which may impact measures of implicit bias.…”
Section: Discussionmentioning
confidence: 97%
“…These members in turn are key in fostering connectedness and trust, which may be lacking due to historical and contemporary acts of medical misconduct and discrimination 76,77,90–92 . Community outreach involves information sharing, which is a 2-way process, examples of which have been reported across a variety of specialties 90–94 . The University of Cincinnati Cochlear Implant Program surveyed African Americans with cochlear implants to identify socioeconomic and cultural barriers to seeking assistance for their hearing loss, specifically cochlear implant surgery.…”
Section: Interventions That Reduce Racial and Ethnic Inequities In Su...mentioning
confidence: 99%